Water-oxygen corrosion resistance behavior of SiCf/SiC composites prepared by different processes - YANG Jinhua; DING Ning; LIU Wei; AI Yingjun; LU Zilong; WANG Han; LIU Hu; ZHOU Yiran; SONG Jiupeng; JIAO Jian (Journal of Aeronautical Materials, 2024)
SiCf/SiC composites were prepared by melt infiltration（MI）process，chemical vapor infiltration combined with precursor infiltration and pyrolysis（CVI+PIP）process and precursor infiltration and pyrolysis（PIP）process，respectively. The microstructures，compositions and properties of SiCf/SiC composites prepared by different processes before and after water-oxygen corrosion at 1300 ℃ were characterized by scanning electron microscopy and its accompanying EDS and X-ray diffractometer. The results show that the distributions of oxygen elements of the fracture surface is obviously different in the composites prepared by different processes，and the phases after corrosion are closely related to the preparation processes. The strength retention rate and modulus retention rate of SiCf/SiC composites prepared by MI process are 84% and 76% after water oxygen corrosion at 1300 ℃ for 50 hours. The strength retention rate of SiCf/SiC composites prepared by CVI+PIP is 64%，and the modulus is increased by 6%. The SiCf/SiC composites prepared by PIP process has a strength retention rate of 49% and a modulus increase of 17%. The composite materials prepared by MI process show oxidation mass gain，while the composite materials prepared by CVI+PIP and PIP process show oxidation mass loss，which are mainly related to its microstructures and compositions.